Juli Legality And Accountability Of The Process Of Destruction Of Evidence Of Illegal Fishing With The Involvement Of A Notary: Legality And Accountability Of The Process Of Destruction Of Evidence Of Illegal Fishing With The Involvement Of A Notary - Juli Moertiono (Faculty of Law, Universitas Pekalongan, 2025)
The destruction of evidence in illegal fishing cases is an important step in law enforcement to ensure that evidence is not misused and in accordance with the provisions of the law. This article discusses the legality and accountability of the process of destroying illegal fishing evidence by highlighting the role of notaries as authorized public officials. This study uses a juridical-normative approach with literature analysis of relevant regulations. The results of the study show that the involvement of notaries contributes significantly to supporting legal transparency and accountability. More specific regulations are needed to increase synergy between notaries and law enforcement agencies in the process of destroying evidence. The destruction of evidence in illegal fishing cases is a very important step in law enforcement to prevent the misuse of evidence and ensure that the legal process runs in accordance with the provisions of the law. Evidence of illegal fishing, such as illegally caught fish, prohibited fishing gear, or boats, often has high economic value and has the potential to cause greater losses if not managed properly. Therefore, the process of destroying evidence not only requires strict supervision, but must also be carried out with valid documentation to provide legal certainty. However, the results of the study also show a number of challenges in practice, including the lack of specific regulations that regulate the involvement of notaries in detail in illegal fishing cases. Therefore, it is necessary to strengthen regulations to increase synergy between notaries and law enforcement agencies, such as the police and prosecutor's office, to ensure that the process of destroying evidence is carried out legally, transparently, and accountably.